Heat transfer by low-frequency phonons and "diffusive" modes in cryocrystal solutions: the Kr–Xe syste - Konstantinov, V.A.; Orel, E.S.; Revyakin, V.P. (Физика низких температур, 2003)
The temperature and volume dependences of the thermal conductivity of the Kr₁–ξ Xeξ solid solution are analyzed in a model in which heat is transferred by low-frequency phonons; above the phonon mobility edge this is done by "diffusive" modes migrating randomly from site to site. The phonon mobility edge w₀ is determined from the condition that the phonon mean free path limited by umklapp processes and scattering on point defects cannot be smaller than one-half the phonon wavelength. The Bridgman coefficientg g = - (∂ln Λ/∂lnV)T is the weighted mean over these modes, whose volume dependences differ strongly. It is shown that the amount of heat transferred by the "diffusive" modes above 100 K is quite large even in pure Kr and it increases with rising temperature and impurity concentration.